Komunitas Mafia Sholawat: Pembinaan Kaum Marginal di Desa Kedungmutih Demak - Sukarman Sukarman; David Mohammad Hatta (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2022)
The phenomenon of street children joining the Punk, Alay, and Cosplay community is one of the social problems in Kedungmutih village, Demak. This research aimed to explain the problem of the Mafia Sholawat community, its background, and its efforts in social extension. The research is qualitative research and field research. The data were analyzed using the descriptive method. The results showed that the community has been established because of some reasons namely, equality of people's fate including children from divorcing parents, lack of parental attention, and the low levels of education. The problem faced by the community is slow to the progress of efforts which need a long time to develop and gradually strategy.